2021
DOI: 10.3390/pr10010069
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Performance, Hydrodynamics, and Free-Surface Effects in Unsteady Flow of a Horizontal Axis Hydrokinetic Turbine

Abstract: This paper presents computational fluid dynamics (CFD) simulations of the flow around a horizontal axis hydrokinetic turbine (HAHT) found in the literature. The volume of fluid (VOF) model implemented in a commercial CFD package (ANSYS-Fluent) is used to track the air-water interface. The URANS SST k-ω and the four-equation Transition SST turbulence models are employed to compute the unsteady three-dimensional flow field. The sliding mesh technique is used to rotate the subdomain that includes the turbine roto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The drop in the power coefficient depends on two factors: the turbine is not completely covered with water, reducing the effective area, and the partial flow separation occurs as the air enters the suction side of the blade, as reported by [16]. A future objective of the present study is to validate the experimental results with a Computational Fluid Dynamics (CFD) model in order to investigate air-water interferences with the Volume of Fluid (VOF) model, which could better interpret the water-air interference and the flow around the HAWT [17,18].…”
Section: Results and Conclusionmentioning
confidence: 72%
“…The drop in the power coefficient depends on two factors: the turbine is not completely covered with water, reducing the effective area, and the partial flow separation occurs as the air enters the suction side of the blade, as reported by [16]. A future objective of the present study is to validate the experimental results with a Computational Fluid Dynamics (CFD) model in order to investigate air-water interferences with the Volume of Fluid (VOF) model, which could better interpret the water-air interference and the flow around the HAWT [17,18].…”
Section: Results and Conclusionmentioning
confidence: 72%
“…ANSYS Fluent software is widely used for CFD modeling of VAHTs, providing advanced turbulence models for simulating complex flow patterns and analyzing blade design and array configuration effects on turbine performance. Research finding by Benavides-Morán et al, point towards ANSYS-Fluent, a commercial CFD package, utilizes the Volume Of Fluid (VOF) model to track air-water interface, revealing decreased power and thrust coefficients with closer rotor immersions [39]. Furthermore, Rodríguez et al, showed that ANSYS-Fluent software, which is a commercially available CFD tool, use VOF model to accurately monitor the interface between air and water.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modelling and simulation of horizontal-and vertical-axis turbines for hydrokinetic applications [10][11][12][13][14].…”
mentioning
confidence: 99%
“…The effects of considering the free surface and support structure on the performance of a horizontal-axis water turbine were considered in [11]. The CFD computations clearly show that for shallow immersion, the presence of the free surface induces a reduction in the power coefficient, as well as it being a constraint for the wake developing, which consequently, recovers at a slower rate than in free-flow conditions, a fact that must be taken into account in the design stage of farms based on hydrokinetic turbines.…”
mentioning
confidence: 99%